Financial Literacy, Usage of Pay-Later Services, and Impulse Buying: The Mediating Role of Shopping Habits - Widiastuti, C. Tri; Sumastuti, Efriyani (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: SPayLater, a Shopee digital payment feature, enables users to buy now and pay later, shaping Generation Z’s shopping habits and contributing to impulsive buying tendencies. Financial literacy plays a crucial role in managing personal finances and avoiding unplanned purchases.Purpose: This study examines the effect of financial literacy and SPayLater usage on impulse buying, with shopping habits serving as a mediating variable among Generation Z consumers in Semarang.Design/methodology/approach: The current study used a quantitative approach, with 100 respondents from Generation Z in Semarang. The survey was conducted using probability sampling with the purposive sampling technique, and the number of respondents was determined using the Cochran formula. Data was collected and analyzed using Smart PLS 3.0.Findings/Results: The results show that financial literacy, SPayLater usage, and shopping habits significantly influence impulse buying. Furthermore, shopping habits mediate the relationships between both financial literacy and SPayLater usage with impulsive buying behavior.Conclusion: Improving financial literacy among Generation Z in Semarang is essential to better regulate shopping habits and reduce impulse buying. Awareness of the risks associated with digital payment tools supports wiser financial decisions.Originality/value: This research emphasizes the mediating role of shopping habits in the relationship between financial literacy and impulse buying, offering new insights into consumer behavior in the context of digital credit services. Keywords: financial literacy, Generation Z, impulse buying, shopping habits, usage of pay-later services